Prostate‐specific membrane antigen expression in melanoma metastases. (6th July 2020) - Snow, Hayden; Hazell, Stephen; Francis, Nicholas; Mohammed, Kabir; O'Neill, Stephanie; Davies, Emma; Mansfield, David; Messiou, Christina; Hujairi, Nabil; Nicol, David; Harrington, Kevin; Smith, Myles
Abstract: Background: Prostate‐specific membrane antigen (PSMA) is a prostatic epithelial protein that is used as a radiotracer (68Ga‐PSMA‐11) for prostate cancer staging. PSMA‐PET/CT (positron emission tomography/computed tomography) performed for prostate cancer has been observed to detect melanoma metastases. The aim of this study was to investigate the performance of PSMA immunohistochemistry on resected melanoma metastases to explore its use as a diagnostic imaging biomarker for melanoma. Methods: A total of 41 specimens with stage III/IV melanoma were stained with PSMA immunohistochemistry. All specimens required both disease and control regions. Two pathologists scored the specimens and a receiver operating characteristic (ROC) curve was plotted. Western blot and multiplex immunofluorescence were also performed. Results: The area under the ROC curve was 0.82, suggesting that PSMA has excellent discriminatory power in melanoma metastases. Sensitivity is 82.9% and specificity 73.2%. Immunohistochemistry and Western blot reveal that PSMA staining in melanoma consistently and most intensely occurs in tumor neovasculature. Multiplex immunofluorescence shows that melanocytes may also weakly express PSMA. Conclusion: The performance of PSMA immunohistochemistry in melanoma metastases contrasts with that reported in prostate cancer studies. This study indicates that PSMA shows promise for use as a novel biomarker in melanoma and justifies further research in the clinical setting with potential as a PET/CT radiotracer and intraoperative fluorescence marker for melanoma.